FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN PROPERTI DAN REAL ESTATE TAHUN 2019-2021 - Nathanael Nathanael; Merry Susanti (Jurnal Paradigma Akuntansi, 2026)
This project aims to obtain empirical evidence about the effect of current ratio, total assets turnover, debt to equity ratio, and firm size on profitability in property and real estate companies listed on the Indonesia Stock Exchange (ISE) for 2019 to 2021 period. This study used purposive sampling as its sampling method. The sample obtained were 46 companies for the 2019 to 2021 period. Data processing on this study held using multiple linear regression analysis assisted by Eviews 12 software. This research showed that debt to equity ratio had a negative and significant effect on profitability, butcurrent ratio, total assets turnover, and firm size had a positive and significant effect on profitability. The outcome of this study is that companies suggested to heed to their own profitability to keep the company activities running and to increase investor’s trust.